Wschodnie patriarchaty wobec sporu dotyczącego tytułu „patriarcha ekumeniczny” - Wolińska, Teresa (Vox Patrum, 2012)
The struggle for primacy in the Universal Church was first started between Rome and Alexandria, but in the middle of 5th Century it was Constantinople that became the most important rival of Rome. The increasing position of the Constantinopolitan bishop was caused by the fact that at the turn of the 4th century the city became capital of the Empire. So, it was the emperor’s interest to give to the bishop of their capital the same rights as those of the bishops of the Old Rome. The growing importance and authority of Constantinopolitan bishops reflected the needs and natural evolution, so it was easily accepted in the Eastern part of the Empire. It was confirmed by the decisions of the two ecumenical councils and by imperial legislation. Hence, the bishops of Constantinople became the most important ones in the East. They rejected papal aspirations to control the whole Church. Popes opposed the growing authority of their rivals in Constantinople. They started to act as St. Peter’s successors and tried to obtain independence from secular authorities. Despite their efforts, the importance of bishops of Constantinople was still increasing. The argument concerning the title of „ecumenical patriarch” was a part of that struggle. Its beginning dates back to the year 483 when pope Felix protested against addressing Accacius, the bishop of Constantinople „ecumenical”. The argument became even more fierce during the pontificates of Pelagius II and Gregory the Great. They both fought against the title used by the patriarchs of Constantinople – John IV the Faster and Cyriacus. Gregory translated the controversial title as „universalis” or „solus” and tried to mount an alliance to fight it. He appealed to Eutychios, the patriarch of Alexandria and to the patriarch of Antioch – Anastasios. The predecessor of the latter, patriarch also named Gregory, just like the pope, did not take part in the argument, but he was in a way cause the cause of it, as the title had been used in the documents from just his trial that were sent to Rome. For Gregory using the title in relation just to the patriarchs of Constantinople sounded diminishing for other bishops. According to the pope, using the title by the patriarchs of Constantinople implied that they would subject other patriarchs and consequently would demand power over the whole Church. Gregory counted that due to that, other patriarchs, particularly those of Antioch and of Alexandria would support him in the argument. He kept writing to both Eulogius and Anastasius. He relied on them the more that he knew both personally and with Eulogius he was even befriended. To his disappointment, both patriarchs kindly refused their support. The problems they had were more important than the question of someone’s title. They felt they might need support from the Byzantine emperor as well as from the patriarch of Constantinople in the struggle with heretics on their own territory and absolutely did not feel threatened by the growing position of the fellow-bishop. Besides, it seems they quite did not understand what the whole problem was about. Consequently, the lack of support from eastern patriarchs and the negative opinion of emperor Maurice resulted in Gregory’s defeat in the argument.